The tree of life : solving science's greatest puzzle - Telford, Maximilian J. (W.W. Norton & Company, 2025)
"Rich with anecdote and infectious enthusiasm, The Tree of Life should delight anyone with even a passing interest in the miracle that is life on our planet." --Henry Gee, author of A (Very) Short History of Life on Earth Taking readers inside one of science's most ambitious projects, a leading evolutionary biologist offers a definitive portrait of life's family tree.